The Effect of Current Ratio and Net Profit Margin on Share Prices at PT Aneka Tambang Tbk Period 2018 - 2021 - Farikhah; Prista Tarigan; Noor Sembiring (Journal of Accounting and Finance Management, 2021)
The purpose of this research is to find out the relationship between financial ratios in the 2018-2021 timeframe. This study aims to draw conclusions whether or not there is evidence that the Current Ratio and Net Profit Margin variables affect stock prices. In this study the methods for data analysis were descriptive statistics, normality test, while the mean difference test used was the paired sample t-test and the Wilcoxon signed rank test. The results of this study indicate thatthe variables Current Ratio and Net Profit Margin have a positive and significant effect on stock prices.